Les mots d’origine bretonne dans l’argot français - Jean-Marc Lecocq (La Bretagne Linguistique, 1991)
Although Breton has borrowed extensively from French for several centuries, there are not many Breton words adopted by this language. Similarly, Breton slang has borrowed quite extensively from French, not only from ancient and modern French, or from dialectal French, but also from slang French, although the number of Breton words in the latter is infinitesimal. However, some people are tempted to explain many slang French words too easily by the Breton language. In this paper, we will study a number of them that are proven to come from Breton.